Tax planning avoid tax contingencies - Quispe Erique, Betty (2021)
This investigation called “Tax planning to avoid tax contingencies of the company Negotiations H&D SAC. Lima, 2020; considered as a general objective Proposing a tax planning to avoid tax contingencies in the company Negociaciones H&D SA C, Lima, 2020. The research is descriptive - propositional, not experimental, the instrument is a questionnaire whose technique is an interview which was applied cash from the company with the intention of providing us with information for the development of our research considering the variables under study. One of the results shows us that there is no tax plan in the company and that for these reasons tax omissions are made to the point of having committed an offense on two occasions in reference to an infraction with the IGV, and Income Tax. Conclusion: the proposal is made to develop a tax plan to avoid future tax contingencies.